Genetic, Morphological and Antigenic Relationships between Mesonivirus Isolates from Australian Mosquitoes and Evidence for Their Horizontal Transmission - Natalee D. Newton; Agathe M. G. Colmant; Caitlin A. O’Brien; Emma Ledger; Devina Paramitha; Helle Bielefeldt-Ohmann; Daniel Watterson; Breeanna J. McLean; Sonja Hall-Mendelin; David Warrilow; Andrew F. van den Hurk; Wenjun Liu; et al. (Viruses, 2020)
The Mesoniviridae are a newly assigned family of viruses in the order Nidovirales. Unlike other nidoviruses, which include the Coronaviridae, mesoniviruses are restricted to mosquito hosts and do not infect vertebrate cells. To date there is little information on the morphological and antigenic characteristics of this new group of viruses and a dearth of mesonivirus-specific research tools. In this study we determined the genetic relationships of recent Australian isolates of Alphamesonivirus 4 (Casuarina virus—CASV) and Alphamesonivirus 1 (Nam Dinh virus—NDiV), obtained from multiple mosquito species. Australian isolates of NDiV showed high-level similarity to the prototype NDiV isolate from Vietnam (99% nucleotide (nt) and amino acid (aa) identity). Isolates of CASV from Central Queensland were genetically very similar to the prototype virus from Darwin (95–96% nt and 91–92% aa identity). Electron microscopy studies demonstrated that virion diameter (≈80 nm) and spike length (≈10 nm) were similar for both viruses. Monoclonal antibodies specific to CASV and NDiV revealed a close antigenic relationship between the two viruses with 13/34 mAbs recognising both viruses. We also detected NDiV RNA on honey-soaked nucleic acid preservation cards fed on by wild mosquitoes supporting a possible mechanism of horizontal transmission between insects in nature.